2013
DOI: 10.1111/apt.12560
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fibrosis on adverse events in patients with hepatitis C treated with telaprevir

Abstract: SUMMARY Background Data about adverse events are needed to optimise telaprevir-based therapy in a broad spectrum of patients. Aim To investigate adverse events of telaprevir-based therapy in patients with and without advanced fibrosis or cirrhosis in a real-world setting. Methods Data on 174 hepatitis C-infected patients initiating telaprevir-based therapy at Mount Sinai and Montefiore medical centres were collected. Biopsy data and FIB-4 scores identified patients with advanced fibrosis. Multivariable fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
11
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 28 publications
5
11
0
Order By: Relevance
“…However, this study finds rates similar to a 2 centerbased study of U.S. CHC patients and a study of CHC treatment in France. 18,24 In a chart review study conducted among HCV patients in the United States, Bichoupan et al (2014) found that 52% of telaprevir patients discontinued therapy early, which is comparable to the approximately 54% of telaprevir patients who did not complete therapy in our study. 18 Similarly, a French multicenter prospective cohort reported early discontinuation rates of 47% among telaprevir patients; however, 42% of boceprevir patients discontinued therapy early, a finding that is lower than the current study.…”
Section: Resource Utilization and Costssupporting
confidence: 79%
See 1 more Smart Citation
“…However, this study finds rates similar to a 2 centerbased study of U.S. CHC patients and a study of CHC treatment in France. 18,24 In a chart review study conducted among HCV patients in the United States, Bichoupan et al (2014) found that 52% of telaprevir patients discontinued therapy early, which is comparable to the approximately 54% of telaprevir patients who did not complete therapy in our study. 18 Similarly, a French multicenter prospective cohort reported early discontinuation rates of 47% among telaprevir patients; however, 42% of boceprevir patients discontinued therapy early, a finding that is lower than the current study.…”
Section: Resource Utilization and Costssupporting
confidence: 79%
“…Previous studies have examined the use of DAAs in specific subpopulations, such as the Veterans Administration (VA) health care system in the United States [14][15][16][17] or in small scale health center-based studies. 18,19 However, few of them investigated the treatment patterns or health care utilization and cost outcomes. This study seeks to contribute to the growing literature on real-world use of DAA therapies by describing the treatment patterns (e.g., initiation, duration, and noncompletion of a minimum duration of therapy as per the …”
Section: Patient Characteristicsmentioning
confidence: 99%
“…[15][16][17] There is more data available regarding the safety profile of the PIs from "real-life" and this data revealed increased risk for severe complications of PI-based treatment in cirrhotic patients. [18][19][20][21] However skin adverse reactions in contrast with other adverse events were comparable with results in clinical trials.…”
Section: Introductionsupporting
confidence: 77%
“…Advanced liver fibrosis was found to be an adverse event associated with anorectal discomfort in Bichoupan et al study. 20 We also found such correlation (OR 4,54 p=0,018). This finding could be due to immune compromise in patients with advanced fibrosis.…”
Section: J Dermatol Case Rep 2014 4 Pp 95-102supporting
confidence: 66%
“…There is evidence suggesting that this is true in reports of the outcomes of triple therapy with regimens including interferon, ribavirin, and a first-generation protease inhibitor. 10,11 Conversely, untreated patients may die of causes unrelated to hepatitis C before they can be expected to experience any benefit of successful therapy. In balance, based on reports of adverse events related to treatment and those documenting slow stage-specific progression of fibrosis secondary to HCV infection and gradual development of hepatic decompensation in many persons with HCV cirrhosis, it is possible that some patients with barriers to HCV treatment might have better or the same outcomes without anti-viral therapy.…”
mentioning
confidence: 99%